In vitro bioactivities of single or combined extracts from three selected Asian vegetables / Norfaizah Mahmud - Norfaizah , Mahmud (2020)
Three underutilized folklore oriental-based vegetables Acalypha indica (AI), Centella asiatica (CA), and Sesbania grandiflora (SG) have been investigated for pharmacological activities relevant to wound healing process and synergistic actions. Single and combination of aqueous (A) and methanol (M) extracts of the three vegetables namely AI-A, CA-A, SG-A, AI-M, CA-M, SG-M, AI-A+CA-A, AI-A+SG-A, CA-A+SG-A, AI-M+CA-M, AI-M+SG-M, and CA-M+SG-M were assessed for stimulation of wound closure by normal human dermal fibroblast (NHDF) cells, antioxidant, protection against hydrogen peroxide (H2O2), stimulation of nitric oxide (NO) from RAW264.7 macrophages and antimicrobial activities. The combined vegetable extracts AI-A+CA-A (90.76%) showed the highest percentage of wound closure, followed by single extract CA-A (89.52%). Pre-treatment of NHDF cells with CA-M at 100 μg/ml offered the best protection against H2O2. At 500 μg/mL, CA-A and combination of CA-A+SG-A successfully induced RAW264.7 cells to produce NO of 17.85 μM and 40.84 μM, respectively. All single and combined vegetable extracts showed weak antibacterial properties against gram-negative (E. coli and S. marcescens) and gram-positive bacteria (B. cereus, B. subtilis, M. luteus, S. aureus, and S. epidermidis). The single and combined vegetable extract showed antifungal-demelanizing activities against Aspergillus niger. AI-A exhibited the highest total phenolic content (TPC) (82.94 mg GAE/g) and moderate reducing activity (61.63 mM Fe (II)/mg) when assessed by ferric reducing antioxidant power (FRAP) assay. Free radical scavenging activity was assessed by 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) assay with AI-A+CA-A exhibited good scavenging activity at IC50 = 379.75 μg/ml and IC50 = 578.7 μg/ml, respectively. Furthermore, identification and characterization of all the single vegetable extracts via UHPLC (LC-MS/MS) system revealed the major components present might be responsible for all the tested bioactivities. The identified major components were phenolic groups such as simple polyphenols, flavonoids (flavones and flavonols), polysaccharides, and triterpenes (asiaticoside and madecassosides). AI-A+CA-A demonstrated synergism (CI < 1) for migration of fibroblast, DPPH free radical scavenging activity and production of NO. AI-A+SG-A and CA-A+SG-A showed synergism for DPPH free radical scavenging activity and production of NO. AI-M+CA-M and AI-M+SG-M demonstrated synergistic interaction for FRAP reducing activity and production of NO. CA-M+SG-M showed synergism for production of NO. These findings demonstrate the potential formulation by one vegetable or combining extracts from two vegetables with multiple functions of accelerating the migration of fibroblast, an excellent source of antioxidants, antimicrobial, and stimulation of NO production for optimum wound healing properties.